2008
DOI: 10.4102/sajbm.v39i3.565
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, support and training requirements of South African expatriates

Abstract: A major issue in international human resource management is the failure of expatriates. The failure rate of expatriates has been reported to range anywhere between 10 and 80 percent, costing multinational enterprises (MNEs) between US$40 000 and US$1 million for each failed assignment. In order to address the problem it is recommended that MNEs provide sufficient preparation, support and training to not only the expatriate but also to their trailing spouses and children. This research has, however, proven that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 9 publications
(2 reference statements)
1
35
0
Order By: Relevance
“…The view that the trailing spouse should be given separate training to adjust to the foreign conditions has also been supported by other researchers (Caligiuri et al 1998;Mendenhall and Stahl 2000;Vögel et al 2008). Adler (2002) emphasized about creating a meaningful life for the spouses in the new and strange host country environment.…”
Section: Literature Reviewmentioning
confidence: 93%
See 3 more Smart Citations
“…The view that the trailing spouse should be given separate training to adjust to the foreign conditions has also been supported by other researchers (Caligiuri et al 1998;Mendenhall and Stahl 2000;Vögel et al 2008). Adler (2002) emphasized about creating a meaningful life for the spouses in the new and strange host country environment.…”
Section: Literature Reviewmentioning
confidence: 93%
“…The importance of spouse support in the adjustment of married expatriates has started receiving importance from researchers in recent times (Huckerby and Toulson 2001;Konopaske et al 2005). One primary concern in this arena is that expatriates who are accompanied by spouses and other members of family may have special requirements from their organizations to provide support for their trailing companions (Bauer and Taylor 2001;Vögel et al 2008). Andreason (2008) suggested that relocation experience of the expatriate and spouse differ by varying degrees.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…The cost of failure expatriate assignments of the project ranges between $250,000 and $1,000,000 [3]. Hereby, the effective expatriation management became an increasingly important task for the international HR department in MNC's.…”
Section: Introductionmentioning
confidence: 99%